The role of tryptophan in Chlamydia trachomatis persistence - Wang, Li; Hou, YingLan; Yuan, HongXia; Chen, Hongliang (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis (C. trachomatis) is the most common etiological agent of bacterial sexually transmitted infections (STIs) and a worldwide public health issue. The natural course with C. trachomatis infection varies widely between individuals. Some infections clear spontaneously, others can last for several months or some individuals can become reinfected, leading to severe pathological damage. Importantly, the underlying mechanisms of C. trachomatis infection are not fully understood. C. trachomatis has the ability to adapt to immune response and persist within host epithelial cells. Indoleamine-2,3-dioxygenase (IDO) induced by interferon-gamma (IFN-γ) degrades the intracellular tryptophan pool, to which C. trachomatis can respond by converting to a non-replicating but viable state. C. trachomatis expresses and encodes for the tryptophan synthase (TS) genes (trpA and trpB) and tryptophan repressor gene (trpR). Multiple genes interact to regulate tryptophan synthesis from exogenous indole, and persistent C. trachomatis can recover its infectivity by converting indole into tryptophan. In this review, we discuss the characteristics of chlamydial infections, biosynthesis and regulation of tryptophan, the relationship between tryptophan and C. trachomatis, and finally, the links between the tryptophan/IFN-γ axis and C. trachomatis persistence.